Lost along the way : a novel - Duffy, Erin (William Morrow, 2016)
"A fresh, funny, and insightful novel about what it really means to be "friends forever" from the acclaimed author of Bond Girl and On the Rocks. All through childhood and adolescence, Jane, Cara, and Meg swore their friendship would stand the test of time. Nothing would come between them, they pledged. But once they hit their twenties, life got more complicated and the BFFs began to grow distant. When Jane eloped with her slick, wealthy new boyfriend and didn't invite her oldest friends to the ceremony, the small cracks and fissures in their once rock-solid relationship became a chasm that tore them apart. Ten years later, when her husband is arrested and publically shamed for defrauding his clients, Jane realizes her life among the one percent was a sham. Penniless and desperate, deserted by the high-society crowd who turn their surgically perfected noses up at her, she comes crawling back to her childhood friends seeking forgiveness. But Cara and Meg have troubles of their own. One of them is trapped in a bad marriage with an abusive husband, while the other can't have the one thing she desperately wants: a baby. Yet as much as they'd love to see Jane get her long overdue comeuppance, Cara and Meg won't abandon their old friend in her time of need. The story of three friends who find themselves on a laugh-out-loud life adventure, Lost Along the Way illuminates the moments that make us, the betrayals that break us, and the power of love that helps us forgive even the most painful hurts"